2009
DOI: 10.1177/0047287509349266
|View full text |Cite
|
Sign up to set email alerts
|

Expectation, Motivation, and Attitude: A Tourist Behavioral Model

Abstract: This study focuses on the previsit stage of tourists by modeling the behavioral process incorporating expectation, motivation, and attitude in the context of Chinese outbound travelers. An expectation, motivation, and attitude (EMA) model is proposed based on a comprehensive literature review. An instrument is developed based on previous tourism and marketing studies as well as focus groups to measure the variables in the EMA model. Data are collected from 1,514 Beijing, Shanghai, and Guangzhou residents. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
285
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(317 citation statements)
references
References 82 publications
23
285
1
8
Order By: Relevance
“…Motivation is perhaps best described as 'psychological/biological needs and wants, including integral forces that arouse, direct and integrate a person's behaviour and activity' (Yoon & Uysal, 2005, p. 46). Several theories or models have been developed to explain motivation (see Gnoth, 1997;Hsu et al, 2010) and early studies such as those of Plog's (1974) 'allocentric2psychocentric', Dann's (1977) 'push2pull', Pearce's (1988) 'travel career ladder ' and Ross and Iso-Ahola's (1991) 'escape seeking' are instrumental. Pearce and Lee (2005) reaffirm the findings of previous studies that tourist push motivations are four-fold in nature (novelty seeking, escape/relaxation, kinship/relationship enhancement and self-development).…”
Section: Motivationsmentioning
confidence: 99%
“…Motivation is perhaps best described as 'psychological/biological needs and wants, including integral forces that arouse, direct and integrate a person's behaviour and activity' (Yoon & Uysal, 2005, p. 46). Several theories or models have been developed to explain motivation (see Gnoth, 1997;Hsu et al, 2010) and early studies such as those of Plog's (1974) 'allocentric2psychocentric', Dann's (1977) 'push2pull', Pearce's (1988) 'travel career ladder ' and Ross and Iso-Ahola's (1991) 'escape seeking' are instrumental. Pearce and Lee (2005) reaffirm the findings of previous studies that tourist push motivations are four-fold in nature (novelty seeking, escape/relaxation, kinship/relationship enhancement and self-development).…”
Section: Motivationsmentioning
confidence: 99%
“…Beijing is known for its high propensity to travel and its trend setting status in lifestyle [68]. Two trained interviewers approached potential respondents outside convenient locations such as high street shopping centers, leisure centers, tourist attractions, and local universities, following a procedure adapted from the study of Hsu et al [68] on the Chinese market.…”
Section: Data Collection and Sample Characteristicsmentioning
confidence: 99%
“…Given the significance of the Chinese market, many studies have focused on Mainland travellers, including research on tourist motivation (Hsu, Cai, & Li, 2010;Hsu & Lam, 2003;Huang & Hsu, 2005;Huang & Hsu, 2009;Lam and Vong, 2009), perception of tour guide performance (Zhang & Chow, 2004), shopping behaviour (Choi, Liu, Pang, & Chow, 2008), and perception of tourism advertisement (der Veen & Song, 2010). Very few studies have been found on investigating magazines as an important information source for travelers, excepting Choi, Lehto, & Morrison (2007) and Bandyopadhyay & Morais (2005).…”
Section: (Table 1 Here)mentioning
confidence: 99%